Automatically Constructed Neural Network Potentials for Molecular Dynamics Simulation of Zinc Proteins - Xu, Mingyuan; Zhu, Tong; Zhang, John Z. H. (Frontiers in Chemistry, 2021)
The development of accurate and efficient potential energy functions for the molecular dynamic simulation of metalloproteins has long been a great challenge for the theoretical chemistry community. Artificial neural network provides the possibility to develop potential energy functions with both the efficiency of the classical force fields and the accuracy of the quantum chemical methods. In this work, neural network potentials were automatically constructed by using the ESOINN-DP method for typical zinc proteins. For the four most common zinc coordination modes in protein, the potential energy, atomic forces and atomic charges predicted by neural network models show great agreement with QM calculations and the neural network potential can maintain the coordination geometry correctly. In addition, MD simulation and energy optimization with neural network potential can be readily used for the structural refinement. The neural network potential is not limited by the function form and complex parameterization process and important quantum effects such as polarization and charge transfer can be accurately considered. The algorithm proposed in this work can also be directly applied to proteins containing other metal ions.